Control system of temperature of locomotives traction frequency converters - Kosmodamianskiy Andrey; Pugachev Alexander; Strekalov Nikolay (MATEC Web of Conferences, 2021)
The features of the control systems of temperature of the traction frequency converters consisted of rectifier, capacitor and voltage source inverter for traction rolling stock are discussed. The induction motor is considered as a load for traction frequency converter. The dependence of the number of thermal cycles from semiconductor junction temperature fluctuations before the failure of the semiconductor device are shown. The topology and operation principle of automatic temperature control system of voltage source inverter semiconductor devices of traction frequency converter are developed and described. The system is based on air forced cooling with the use of fan or blower as an executive regulation device. The main feature of the proposed system is the additional reference of switching frequency that allows to reduce the semiconductor temperature fluctuations. The elements of switching frequency control loop are chosen and evaluated, the recommendations on practical implementations are given. Simulation of automatic temperature control system in Matlab with both references of semiconductor junction temperature and its fluctuation was carried out with all essential nonlinearities of induction motors and semiconductor devices taken into account. Results of simulation are included and discussed.